PTIMIZING THE ROLE OF KODIM 0612/TSM IN HELPING LOCAL GOVERNMENT TO ACHIEVE NATIONAL FOOD SECURITY: OPTIMALISASI PERAN KODIM 0612/TSM DALAM MEMBANTU PEMERINTAH DAERAH GUNA MEWUJUDKAN KETAHANAN PANGAN NASIONAL - Rohmanu; Guntur Eko Saputro; Bangun P. Hutajulu (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Food security is a fundamental aspect in maintaining national stability, especially in Indonesia. The role of the Indonesian National Army (TNI), through regional command units such as Kodim, is crucial in supporting local government programs aimed at food security. This study aims to analyze the role of Kodim 0612/Tasikmalaya in assisting the Local Government (Pemda) of Tasikmalaya Regency in achieving food security. The study also evaluates Kodim's contributions, identifies the challenges faced, and formulates strategies for optimizing its role. The research method used is a qualitative approach with descriptive-analytical techniques. Data was collected through in-depth interviews with Kodim 0612/Tasikmalaya personnel, Pemda officials, and food security experts, along with literature review and field observations. The results of the study show that Kodim 0612/Tasikmalaya plays an active role in providing technical assistance for agriculture, training farmers, and overseeing the distribution of production facilities to maintain food price stability. The main challenges faced include limited human resources, lack of coordination with Pemda, and geographical and infrastructure challenges. The optimization of Kodim's role can be achieved through improved coordination between Kodim and Pemda, strengthening personnel capacity through intensive training, and utilizing information technology for monitoring and distribution efficiency. This study recommends increasing personnel capacity and competence, as well as developing a technology-based monitoring system to effectively measure the success of food security programs.